Religion, Belonging, and Active Citizenship: A Systematic Review of Literature on Muslim Youth in Australia - Ozalp, Mehmet (Religions, 2021)
Muslim youth have been under scrutiny over the last two decades from a radicalisation and countering violent extremism lens. This bias has largely carried itself to research conducted on Muslim youth in the West. This article undertakes a systematic review and analysis of literature conducted on Muslim youth in the West and in Australia in the last two decades since 11 September 2001. The body of literature in this field can be grouped under three main themes: (1) the impact of terrorism policies and discourse on Muslim youth and their disengaged identities, (2) the relationship between religion (Islam) and civic engagement of Muslim youth, and (3) Muslim youth as active citizens. An important conclusion of this review is that most of the research is dated. There have been significant changes in the development of youth as they quickly evolve and adapt. The systematic review of literature exposed a number of gaps in the research: the current literature ignores generic adolescent factors and external social factors other than Islam that also influence Muslim youth; studies that examine both online and traditional activism and volunteering space are needed to understand the dynamics of change and shift; research needs to focus on Muslim youth who were born and raised in Australia rather than focus only on migrant youth; the ways some Muslim youth use their unique sense of identity as Australian Muslims to become successful citizens engaged in positive action is not known; how Muslim youth use avenues other than their faith to express themselves in civic engagement and their commitment to society is underexplored; it is not known the degree to which bonding networks influence the identity formation and transformation of Muslim youth; there is no research done to examine how adult-youth partnership is managed in organisations that successfully integrate youth in their leadership; there is a need to include Australian Muslim youth individual accounts of their active citizenship; there is a need to understand the process of positive Muslim youth transformations as a complement to the current focus on the radicalisation process. Addressing these gaps will allow a more complete understanding of Muslim youth in the West and inform educational and social policies in a more effective manner.